Analysis Implementasi English Area dalam Meningkatkan Speaking Skill dan Self- Regulated Mahasiswa Pendidikan Bahasa Inggris Institut Pendidikan Nusantara Global - Mul Muliadi; Ahmad Zuhri Rosyidi (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this research is to obtain an overview of improving speaking skills and self-regulated students of English education of Institute Pendidikan Nusantara Global in the implementation of English area. This research is descriptive qualitative research. The research was conducted at the Institute Pendidikan Nusantara Global (IPNG) Aikmual Lombok Tengah NTB. After the data is obtained the researcher further analyzes and tests the validity of the data by validating the data using data source triangulation tests and data collection techniques. The data of this research collected through practice test (Themes: environment, culture, health, education) and non-test (interview guidelines, self-regulated questionnaires and documentation studies). Based on the results of test and data analysis it can be concluded that the ability of students in improving speaking skills using English area is very effective and needs to be applied and developed. The application of English area can improve students’ speaking skills and self-regulated.